Manipulation of avocado (Persea americana Mill.) trees for out of season fruit production - Robbertse, P.J. (Petrus Johannes), 1932- (University of Pretoria, 2013)
Dissertation (MSc (Agric) Horticultural Science)--University of Pretoria, 2005.